A hybrid health service accreditation program model incorporating mandated standards and continuous improvement: interview study of multiple stakeholders in Australian health care. (5th June 2015) - Greenfield, David; Hinchcliff, Reece; Hogden, Anne; Mumford, Virginia; Debono, Deborah; Pawsey, Marjorie; Westbrook, Johanna; Braithwaite, Jeffrey
SUMMARY: The study aim was to investigate the understandings and concerns of stakeholders regarding the evolution of health service accreditation programs in Australia. Stakeholder representatives from programs in the primary, acute and aged care sectors participated in semi‐structured interviews. Across 2011–12 there were 47 group and individual interviews involving 258 participants. Interviews lasted, on average, 1 h, and were digitally recorded and transcribed. Transcriptions were analysed using textual referencing software. Four significant issues were considered to have directed the evolution of accreditation programs: altering underlying program philosophies; shifting of program content focus and details; different surveying expectations and experiences and the influence of external contextual factors upon accreditation programs. Three accreditation program models were noted by participants: regulatory compliance; continuous quality improvement and a hybrid model, incorporating elements of these two. Respondents noted the compatibility or incommensurability of the first two models. Participation in a program was reportedly experienced as ranging on a survey continuum from "malicious compliance" to "performance audits" to "quality improvement journeys". Wider contextual factors, in particular, political and community expectations, and associated media reporting, were considered significant influences on the operation and evolution of programs. A hybrid accreditation model was noted to have evolved. The hybrid model promotes minimum standards and continuous quality improvement, through examining the structure and processes of organisations and the outcomes of care. The hybrid model appears to be directing organisational and professional attention to enhance their safety cultures. Copyright © 2015 John Wiley & Sons, Ltd.